Vaginal laxity: which measure of levator ani distensibility is most predictive?. (1st May 2020) - Manzini, C.; Friedman, T.; Turel, F.; Dietz, H. P.
ABSTRACT: Objective: To assess the predictive value of measures of levator hiatal distension at rest and on maximum Valsalva maneuver for symptoms of vaginal laxity. Methods: This was a retrospective study of women seen at a tertiary urogynecological unit. All women underwent a standardized interview, clinical examination and four‐dimensional translabial ultrasound examination. Area, anteroposterior diameter (APD) and coronal diameter (CD) of the levator hiatus were measured at rest and on maximum Valsalva maneuver in the plane of minimal hiatal dimensions using the rendered volume technique, by an operator blinded to all clinical data. The association between levator hiatal measurements and vaginal laxity was assessed, and receiver‐operating‐characteristics (ROC)‐curve analysis was used to determine their predictive value. Results: Data from 490 patients were analyzed. Mean age was 58 (range, 18–88) years, and vaginal laxity was reported by 111 (23%) women. Measurements obtained on maximum Valsalva were significantly larger in women who reported vaginal laxity than in those who did not, with mean levator hiatal area, APD and CD of 30.45 ± 8.74 cm 2, 7.24 ± 1.16 cm and 5.60 ± 0.89 cm, respectively, in the vaginal‐laxity group, compared with 24.84 ± 8.63 cm 2, 6.64 ± 1.22 cm and 5.01 ± 0.97 cm in the no‐laxity group ( P < 0.001 for all). Measurements obtained at rest were not significantly different between the groups. Multiple logistic regression analysis controlling for age, body mass index, vaginal parity and levator avulsion confirmed these results. The best regression model for the prediction of vaginal laxity included age, vaginal parity and levator hiatal area on maximum Valsalva. ROC‐curve analysis of levator hiatal measurements on maximum Valsalva in the prediction of vaginal laxity demonstrated areas under the curve of 0.68 (95% CI, 0.63–0.73) for area, 0.63 (95% CI, 0.57–0.68) for APD and 0.68 (95% CI, 0.62–0.73) for CD. Conclusions: Levator hiatal area on maximum Valsalva seems to be the measure of levator ani distensibility that is most predictive of symptoms of vaginal laxity. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.